Redefining HRM in the Digital Age: Leveraging Technology for Effective Talent Management - Fajar Pasaribu; Masriadi; Kristina Sedyastuti; Nur Hamzah; Alfin Reza Syahputra (Global Writing Academica Researching & Publishing, 2023)
In response to the transformation of the human resource management (HR) paradigm in the digital era, this research explores the impact of technological change on talent management and employee performance in the context of modern organizations. This research aims to identify emerging challenges and opportunities and formulate effective strategies for managing diversity as a source of innovation and productivity. This research adopts a descriptive qualitative approach with data derived from research results and relevant previous studies. The data collection process involved a thorough literature review, and the results of the data analysis provide a comprehensive picture of the role of technology in the transformation of talent management. The research results found that the transformation of the human resource management (HR) paradigm in the digital era has had a significant impact on organizational dynamics. The evolution of management models from traditional to digital, the use of technology in recruiting and developing employee skills, and the use of technology-based performance management are critical shifts in responding to changing demands. Employee diversity in the digital era brings challenges that need to be managed carefully. Managing the risk of inequality and increasing inclusiveness are key aspects of creating a competitive work environment.